2007
DOI: 10.1152/jn.00349.2006
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation (LTP) in the Central Amygdala (CeA) Is Enhanced After Prolonged Withdrawal From Chronic Cocaine and Requires CRF1 Receptors

Abstract: . The amygdala is part of the brain reward circuitry that plays a role in cocaine-seeking and abstinence in animals and cocaine craving and relapse in humans. Cocaine-seeking is elicited by cocaine-associated cues, and the basolateral amygdala (BLA) and CeA are essential in forming and communicating drugrelated associations that are thought to be critical in long-lasting relapse risk associated with drug addiction. Here we simulated a cue stimulus with high-frequency stimulation (HFS) of the BLA-CeA pathway to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…We (Fu and Shinnick-Gallagher 2007) demonstrated at the basolateral amygdala to central amygdala nucleus (Fig. 5, #a) synapse that endogenous CRH co-released during high frequency stimulation was blocked by the selective CRH 1 antagonist NBI30775.…”
Section: Crh and Ltpmentioning
confidence: 76%
See 1 more Smart Citation
“…We (Fu and Shinnick-Gallagher 2007) demonstrated at the basolateral amygdala to central amygdala nucleus (Fig. 5, #a) synapse that endogenous CRH co-released during high frequency stimulation was blocked by the selective CRH 1 antagonist NBI30775.…”
Section: Crh and Ltpmentioning
confidence: 76%
“…CRH has been suggested to be responsible for "Priming" (Blank et al 2002;Rainnie et al 2004), and as such may also contribute to a functional synonym for priming, namely, "Metaplasticity" (Abraham and Bear 1996). CRH has been implicated directly in long-term potentiation (LTP, Rebaudo et al 2001;Fu et al 2006;Pollandt et al 2006;Wang et al 2000;Wang et al 1998) and long-term depression (LTD, Miyata et al 1999;Schmolesky et al 2007). …”
Section: Semantics Associated With Crh Synaptic Functionsmentioning
confidence: 99%
“…Fu et al (2007) used HFS in the neural afferents connecting the basolateral amygdala (BLA) and the CeA (BLA-CeA pathway) to simulate cue-stimuli, associated to cocaine consumption. In animals previously treated with intermittent repeated cocaine, HFS enhanced LTP in the BLA-CeA terminals after long-term withdrawal, but not shortly after cocaine cessation.…”
Section: Crf-related Plasticity In the Cea And Bnst During Abstinencementioning
confidence: 99%
“…In animals previously treated with intermittent repeated cocaine, HFS enhanced LTP in the BLA-CeA terminals after long-term withdrawal, but not shortly after cocaine cessation. CRF-R1 mediated the enhancement of synaptic strength during withdrawal, an effect requiring the activation of NMDA GLU receptors and N-type voltage-gated calcium channels (Fu et al 2007). These results are in agreement with those published by other authors (Pollandt et al 2006) and suggest a role for CRF in encoding cocaine withdrawal related information in the CeA synapses.…”
Section: Crf-related Plasticity In the Cea And Bnst During Abstinencementioning
confidence: 99%
“…These behavioral data seemed to be in accordance with earlier data where cocaine impaired hippocampal long-term potentiation (LTP, Smith et al 1993). However, more recently, cocaine administration has been shown to facilitate LTP in the prefrontal cortex , amygdala (Fu et al 2007), and even in the hippocampus (Thompson et al 2002). In fact, previous results from our laboratory and those of others have shown that cocaine self-administration induces an enhancement of LTP in hippocampal slices (del Olmo et al 2006b;Thompson et al 2004) and that this enhancement of LTP after cocaine self-administration appears to be maintained even during the extinction of this behavior (del Olmo et al 2006b).…”
Section: Introductionmentioning
confidence: 75%